Currency hedging and the Danish pension sector - Sigurd Anders Muus Steffensen; Birthe Merethe Jensen; Asger Munch Grønlund (Danmarks Nationalbank, 2024)
The ratio of pension assets to GDP in Denmark is the highest among OECD countries. Danish pension funds invest more than half of the country's pension wealth in foreign assets, giving rise to exchange rate risks that are managed using financial instruments. We study the currency hedging behaviour of the Danish pension sector and show that it differs with respect to exposures in dollar and euro, given Denmark's fixed exchange rate against the euro. Additionally, we find a statistically and economically significant relation between US stock price movements and flows of kroner from FX rebalancing.
Keywords: 330; Pension fund; foreign assets; hedging; currency risk; Denmark; Pensionskasse; Auslandsvermögen; Hedging; Währungsrisiko; Dänemark